A joint experimental and theoretical study on the electronic structure and photoluminescence properties of Al-2(WO4)(3) powders - Batista, F. M. C.; La Porta, F. A. [UNESP]; Gracia, L. [UNESP]; Cerdeiras, E.; Mestres, L.; Li, M. Siu; Batista, N. C.; Andres, J.; Longo, E. [UNESP]; Cavalcante, L. S. (Elsevier B.V., 2015)
In this paper, aluminum tungstate Al-2(WO4)(3) powders were synthesized using the co-precipitation method at room temperature and then submitted to heat treatment processes at different temperatures (100, 200, 400, 800, and 1000 degrees C) for 2 h. The structure and morphology of the powders were characterized by means of X-ray diffraction (XRD), Rietveld refinement data, and field emission scanning electron microscopy (FE-SEM) images. Their optical properties were examined with ultraviolet-visible (UV-vis) diffuse reflectance spectroscopy and photoluminescence (PL) measurements. XRD patterns and Rietveld refinement data showed that Al2(W04)3Al(2)(WO4)(3) powders heat treated at 1000 C for 2 h have a orthorhombic structure with a space group (Pnca) without the presence of deleterious phases. FE-SEM images revealed that these powders are formed by the aggregation of several nanoparticles leading to the growth of microparticles with irregular morphologies and an agglomerated nature. UV-vis spectra indicated that optical band gap energy increased from 3.16 to 3.48 eV) as the processing temperature rose, which was in turn associated with a reduction in intermediary energy levels. First-principle calculations were performed in order to understand the behavior of the PL properties using density functional theory at the B3LYP calculation level on periodic model systems and indicate the presence of stable electronic excited states (singlet). The analyses of the band structures and density of states at both ground and first excited electronic states provide insight into the main features, based on structural and electronic order–disorder effects in octahedral [AlO6] clusters and tetrahedral [WO4] clusters, as constituent building units of this material.
Keywords: Al-2(WO4)(3); Electronic structure; Clusters; DFT calculations; Photoluminescence